Delirium Transitions in the Medical ICU. Issue 1 (January 2015) - Kamdar, Biren B.; Niessen, Timothy; Colantuoni, Elizabeth; King, Lauren M.; Neufeld, Karin J.; Bienvenu, O. Joseph; Rowden, Annette M.; Collop, Nancy A.; Needham, Dale M.
<x xml:space="preserve">Abstract</x> Objectives: Disrupted sleep is a common and potentially modifiable risk factor for delirium in the ICU. As part of a quality improvement project to promote sleep in the ICU, we examined the association of perceived sleep quality ratings and other patient and ICU risk factors with daily transition to delirium. Design: Secondary analysis of prospective observational study. Setting: Medical ICU over a 201-day period. Patients: Two hundred twenty-three patients with greater than or equal to one night in the medical ICU in between two consecutive days of delirium assessment. Interventions: None. Measurements and Main Results: Daily perceived sleep quality ratings were measured using the Richards-Campbell Sleep Questionnaire. Delirium was measured twice daily using the Confusion Assessment Method for the ICU. Other covariates evaluated included age, sex, race, ICU admission diagnosis, nighttime mechanical ventilation status, prior day's delirium status, and daily sedation using benzodiazepines and opioids, via both bolus and continuous infusion. Perceived sleep quality was similar in patients who were ever versus never delirious in the ICU (median [interquartile range] ratings, 58 [35–76] vs 57 [33–78], respectively; p = 0.71), and perceived sleep quality was unrelated to delirium transition (adjusted odds ratio, 1.00; 95% CI, 0.99–1.00). In mechanically ventilated patients, receipt of a continuous benzodiazepine and/or opioid infusion was associated with delirium transition (adjusted odds ratio, 4.02; 95% CI, 2.19–7.38; p < 0.001), and patients reporting use of pharmacological sleep aids at home were less likely to transition to delirium (adjusted odds ratio, 0.40; 95% CI, 0.20–0.80; p = 0.01). Conclusions: We found no association between daily perceived sleep quality ratings and transition to delirium. Infusion of benzodiazepine and/or opioid medications was strongly associated with transition to delirium in the ICU in mechanically ventilated patients and is an important, modifiable risk factor for delirium in critically ill patients.